A estabilização da tutela antecipada antecedente concedida em face da Fazenda Pública - Dall´Acqua, Thaís Ghelfi (2019)
Our study aims to discuss the stabilization of interlocutory advance injunction, incorporated in the Brazilian legal system by the 2015 Code of Civil Procedure, thereby associating it with the special condition of the Treasuries, investigating its application and proposing limits to its incidence. In order to assist such an analysis, this investigation was organized in four chapters. The second chapter deals with preliminary aspects of provisional injunction, highlighting its relevance for the implementation of rights and its relation to summary cognition, as well as drawing a brief history of provisional injunction in the Brazilian procedural system. The third chapter approaches general aspects of provisional injuction in the 2015 Code of Civil Procedure, identifying and characterizing their types. In the fourth chapter, the stabilization concept as such is studied, pointing out the existence of similar concepts in the procedural systems of other countries, dealing with their requirements, limits and procedures. In the fifth and last chapter before conclusion, the conception of Treasury will be examined, addressing important principles that regulate Public Administration, discussing their main procedural prerogatives and, finally, analyzing the application of stabilization of the interlocutory advance injunction whenever granted in the face of the State